The Anti-Atlantis: Suki Kim, North Korea, and Immersion Narrative. (7th May 2019) - Wilson, Christopher P
Abstract: In 2014, novelist and journalist Suki Kim released Without You, There Is No Us, a book that recounted her six-month investigative journey posing as an evangelical Christian teacher within an all-male academy just outside Pyongyang, North Korea. The book was widely praised, even rising to the New York Times ' best-seller list. But in the aftermath of its release, Kim also felt the need to respond to the way the book was marketed and received, and to suggestions by some that she had not written a "journalistic" exposé at all but, rather, a narrow and perhaps even unethical memoir of ethnic self-discovery. Pivoting off Kim's rebuttal—in a reply titled "The Reluctant Memoirist" in The New Republic —this essay examines this misreading and suggests it has much to say about how Kim's critics conceive of so-called "immersion" journalism and its relationship to ethnicity, gender, and race. Without You is read as a hybrid immersion narrative that interweaves complex plots about family postmemory and Korean partition into a story about Kim's teaching experience and the stifling of intimacy and even love in North Korea's militarized and isolationist society.